2015
DOI: 10.1039/c4cc08629e
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free cascade construction of C–C bonds by activation of inert C(sp3)–H bonds

Abstract: A new synthetic strategy for C-C bond formation has been developed via a free radical cascade process under metal-free conditions. Activation of inert C(sp(3))-H/elimination of SO2/C-C bond formation were achieved in sequence in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…4 In addition, transition metalmediated reactions have also been applied to the field of aryl migration reactions. For example, Nevado's group has reported a copper-catalyzed aryl migration reaction by using Togni's reagent 5 to generate trifluoromethyl radical species.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, transition metalmediated reactions have also been applied to the field of aryl migration reactions. For example, Nevado's group has reported a copper-catalyzed aryl migration reaction by using Togni's reagent 5 to generate trifluoromethyl radical species.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Our group reported the tandem oxidative C(sp 3 )-H bond activation/SO 2 elimination/C(sp 2 )-C(sp 3 ) bond formation reaction of simple cyclanes and N-phenyl-Ntosylmethacrylamides under metal-free conditions (Scheme 1(d)). 11 The spirodienone motif is widely found in natural products and organic molecules, which offers a base for the construction of organic compounds with a complex structure. 12 Especially, much effort has been spent on dearomatizing spirocyclization of phenol derivatives, which provides direct access to the highly valuable spirodienone motif and can be used in complex total syntheses.…”
mentioning
confidence: 99%
“…It was also found that DSSCs with pure MWCNTs cathode displayed a PCE of 3.71%, which was comparable with the results reported in the literature (2.69%, 2.87%, and 3.94%). [45][46][47][48] It indicates that the www.advancedsciencenews.com www.solar-rrl.com commercial MWCNTs without any special treatment should not be a high-performance electrocatalyst for IRR. The combination of perovskite and carbon material greatly enhanced the IRR activity as compared with the individual component, which can be assigned to the fact that perovskite oxide provided the active sites for IRR and the carbon material served as a highly conductive substrate as demonstrated in our previous study.…”
Section: Resultsmentioning
confidence: 99%